PENGARUH PEMBIAYAAN BIDANG PENDIDIKAN, KESEHATAN DAN PEKERJAAN UMUM TERHADAP TINGKAT KEMISKINAN DI WILAYAH KABUPATEN PESISIR DI KALIMANTAN BARAT - B61112029, Syarif Muhammad Zein Alkadrie (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT Thetitle of thisresearch:The Effect ofFinancingof Education, HealthandPublic working (facillities and hausing) AgainstPoverty inCoastal RegionDistrictin West Kalimantan," By: SyarifMuhammadZeinAlkadrie, Magister Economics of Economic Faculty’s  Tanjungpura Univeresity Pontianak. The government financing of education, health and public works spending is mandatory and is increasing every year, while the poverty rate decreased slowly, there are characteristic differences between coastal and non coastal districts in West Kalimantan. The purpose of this study was to determine the effect of financing education, health and public works to the existing number of poor people in coastal districts of West Kalimantan. This type of research is a descriptive study, and the method is Multiple Linear Regression analysis with a pool data (data panel), the data source of the report on the realization of financing the Indonesian Directorate General of Treasury Balance. The results showed that the financing both of education and health are negatively affect the level of poverty with the same coefficient as -0.014. This means that any changes or additions to the unit (One Million) financing education and / or health or cause a reduction of 0,014 units 14 poverty. While the effect of the financing of public works is positive with regression coefficient of 0.012, meaning that changes in the financing of public works unit causes additional poverty rate of 0.012, or the addition of poor people by 12 people. Results of simultaneous significance testing of the three variables showed a significant effect simultaneously. The strength of the influence of the three variables indicated by the coefficient of determination (adjR2= 0.352), meaning that the variable education financing (X1it), health (X2it), and public works (X3it) only 35.20% explain the dependent variable Y (the poverty rate) while the rest (64.80%) is explained or influenced by other factors. Keywords:       Poverty, education financing, health financing, the financing of public works.